Covariation patterns of phytoplankton and bacterioplankton in hypertrophic shallow lakes. Issue 11 (20th August 2020) - Schiaffino, M R; Huber, P; Sagua, M; Sabio y García, C A; Reissig, M
ABSTRACT: The aim of this work was to assess the temporal patterns in the community composition of phytoplankton (PCC) and bacterioplankton (BCC) in two interconnected and hypertrophic Pampean shallow lakes in Argentina. Factors shaping their community dynamics and community temporal covariations were also analysed. We performed 4 years of seasonal samplings (2012–2016) and communities were studied by the Utermöhl approach (PCC) and Illumina MiSeq sequencing (BCC). We found marked seasonal variations in both communities and inter-annual variations with decreasing microbial community similarities during the study. We also observed covariation in community-level dynamics among PCC and BCC within and between shallow lakes. The within-lake covariations remained positive and significant, while controlling for the effects of intrinsic (environmental) and extrinsic (temporal and meteorological) factors, suggesting a community coupling mediated by intrinsic biotic interactions. Algal-bacterial associations between different taxa of phytoplankton and bacterioplankton within each lake were also found. PCC was mainly explained by pure regional extrinsic (17–21%) and intrinsic environmental (8–9%) factors, while BCC was explained by environmental (8–10%) and biotic interactions with phytoplankton (7–8%). Our results reveal that the influence of extrinsic regional factors can be channeled to bacterioplankton through both environmental (i.e. water temperature) and phytoplankton effects. Abstract : Aquatic microorganisms moving at the same rhythm.